The perception of Johannesburg residents on the Challenges and Opportunities of Active Community Involvement in the Development of City Branding - Mncube, Kwandokuhle (The IIE, 2022)
Countries and cities compete in an almost-open market for investment and tourists in a globalised world. As a result, having a consistent and engaging brand is just as vital for them as it is in the private sector. However, cities in South Africa are trying to establish their brands, torn between the desire to be "world-class" and the desire to be responsive to all residents. Various research in South Africa have sought to investigate the potentials for community-based city development, but little has been done to explore the problems and prospects of that development. As a result, the goal of this study paper was to identify the significant obstacles and opportunities of city branding development in Johannesburg. In order to achieve these objectives, both primary and secondary data were generated through qualitative (in depth interview and journal papers as well as internet searches). The chosen data collection method was done in order to give the respondents the space and the freedom to express their different perceptions of their experiences in the City of Johannesburg, and therefore producing more insight for the research. The findings suggest that there are various challenges which obstruct community participation in city branding. Some of the most prominent challenges that were highlighted by the community include a lack of information and awareness and corruption.
Keywords: Customer behaviour; Tourism; Marketing; Branding